Uji Reliabilitas Barriers to Seeking Psychological Help Scale (BSPHS) versi Bahasa Indonesia - Gusti Ayu Ardhia Candra Trikusuma; Nurul Hartini (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
The increasing prevalence of mental health issues among Indonesian young adults lacks a corresponding effort in seeking professional aid. Hence, understanding the factors inhibiting their access to psychological assistance is crucial. This research aims to to examine the validity and reliability of the Indonesian version of the Barriers to Seeking Psychological Help Scale (BSPHS) to discern the inhibiting factors for young adults in seeking psychological assistance from professionals in Indonesia. The study involves 229 participants aged 18 to 32. Results indicate that the Bahasa Indonesia BSPHS version is both valid and reliable in measuring barriers to seeking psychological help for young adults, with Pearson correlation ranging from 0.409 to 0.719 and a Cronbach’s Alpha coefficient of 0.894. Factors inhibiting help-seeking that exhibit high to very high reliability scores include fear of societal stigma, trust in professionals, self-disclosure difficulty, lowered self-esteem, and lack of knowledge.